First report of cholesterol deficiency associated APOB mutation causing calf mortality in Indian Holstein Friesian population - KUMAR, ANSHUMAN; GUPTA, I D; KUMAR, SUSHIL; VINEETH, M R; D, RAVI KUMAR; MOHAN, GOVIND; JAYAKUMAR, S; NIRANJAN, SAKET KUMAR (The Indian Journal of Animal Sciences, 2021)
Cholesterol deficiency is a new monogenic autosomal recessive inherited defect in Holstein cattle and is associated with chronic and recurrent diarrhea followed by death of calves during the first six months of life. We have successfully screened the causative mutation for cholesterol deficiency in indigenous, exotic and crossbred cattle of India. This is the first report about the presence of APOB mutation causing calf mortality in the Indian Holstein Friesian population. The mutation associated with cholesterol deficiency was not detected in any of indigenous breeds of cattle suggesting that the mutation could be specific to Holstein Friesian breed only. The occurrence of causal mutation for cholesterol deficiency in one of the Holstein Friesian bull under study (with carrier frequency of 1.67%) clearly indicates that mutation has already been transmitted into Indian Holstein-Friesian population. In our opinion it is the right time to take stringent actions in order to check its further spread. Further, this study accentuates the need for regular screening of existing as well as importing breeding bulls, especially of Holstein-Friesian lineage, for CDH genetic defect before introduction of bulls into genetic improvement programs. It is also highly recommended that the screening for CDH mutation must be made mandatory for all the semen producing/importing agencies under the minimum standards for production of bovine semen.